Proceedings of the Twenty-Ninth International Joint Conference on Artificial Intelligence 2020
DOI: 10.24963/ijcai.2020/660
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Historical Photo Identification with Face Recognition and Crowdsourced Human Expertise (Extended Abstract)

Abstract: Identifying people in historical photographs is important for interpreting material culture, correcting the historical record, and creating economic value, but it is also a complex and challenging task. In this paper, we focus on identifying portraits of soldiers who participated in the American Civil War (1861-65). Millions of these portraits survive, but only 10-20% are identified. We created Photo Sleuth, a web-based platform that combines crowdsourced human expertise and automated face recognition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Moddrop [20] is based on multi-scale and multi-modal deep learning for gesture detection and localization. Photo Sleuth [48] is a web-based platform for user authentication, which can help users successfully identify unknown portraits. Song [49] utilized a single stereo camera to track the body and hands and adopt modelbased methods and particle filters to reconstruct body posture in 3D space to achieve human-computer interaction.…”
Section: Vision-based Motion Recognitionmentioning
confidence: 99%
“…Moddrop [20] is based on multi-scale and multi-modal deep learning for gesture detection and localization. Photo Sleuth [48] is a web-based platform for user authentication, which can help users successfully identify unknown portraits. Song [49] utilized a single stereo camera to track the body and hands and adopt modelbased methods and particle filters to reconstruct body posture in 3D space to achieve human-computer interaction.…”
Section: Vision-based Motion Recognitionmentioning
confidence: 99%
“…Users can carefully inspect individual search results to determine whether they are facially similar to the query photo and whether the biographical information (e.g., military service records) line up with the visual clues of the query photo (e.g., uniform insignia). However, prior work has shown that the correct match is often ranked beyond the top-5 and top-50 face recognition results [4,5]. SleuthTalk provides an intelligent user interface to allow users add any potential matches to a shortlist from the facial recognition results and then create a project for analyzing these shortlisted candidates in a focused manner.…”
Section: Intelligent Shortlistsmentioning
confidence: 99%